Psychopathological Aspects of Somatization in the Works of the Department of Psychiatry of Irkutsk State Medical Institute in the First Half of the 20th Century – from the Origins of the Psychosomatic Medicine to the Present - V. S. Sobennikov (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
The article discusses modern problems of dimensional diagnosis of somatoform disorders including the vagueness of the criteria and the lack of reliance on pathogenetic differences in the selection of separate classification categories. An ongoing discussion on the necessity of revision of the boundaries and of “redistribution” of some somatoform disorders into different categories in accordance with their psychopathological relationship is associated with these problems. As a promising change in the diagnostic criteria of the DSM-V classification, the emphasis is shifted to psychological and behavioral characteristics, which is assessed as an actualization of the classical descriptive diagnostics methodology. As a confirmation of the significance of this, an analysis of the psychopathological study of Irkutsk psychiatrists of the first half of the 20th century, devoted to the delusion of obsession, is given. In 1935, the head of the Department of Psychiatry at the Irkutsk Medical Institute V.S. Deryabin and his student I.S. Sumbaev published a scientific work “Delirium of obsession and somatic sensations”. The authors substantiate the intimate relationship of traditionally understood sensual hysterical and ideatorial hypochondriacal mechanisms in the formation of an integral clinical picture of somatoform disorders. The use of descriptive diagnostics many decades before the introduction of ICD-10 proves the pathogenetic unity of hysterical (sensory) and hypochondriacal (ideatorial) formations within the psychosomatic register of disorders and the legitimacy of combining phenomenologically different states into a circle of somatoform disorders.